Correction: Boosting the solar water oxidation performance of a BiVO 4 photoanode by crystallographic orientation control (Energy and Environmental Science (2018) 11 (1299-1306) DOI: 10.1039/C8EE00125A) - Han, Hyun Soo; Shin, Sun; Kim, Dong Hoe; Park, Ik Jae; Kim, Ju Seong; Huang, Po Shun; Lee, Jung Kun; Cho, In Sun; Zheng, Xiaolin (Energy and Environmental Science, 2019)
The authors regret that citations were omitted from the caption of Fig. 4, parts (c) and (d). The caption of Fig. 4 is updated as given below: Fig. 4 Surface modification of a p-BVO photoanode. (a) Top-view SEM image and (b) AFM topography and height profiles of surface-etched p-BVO. The striped pattern had a span of B70 nm and pitches of B30 nm. J-V curves of best-performing BVO-based photoanodes (c) without electrocatalysts1-4 and (d) with electrocatalysts reported to date.1,4-6 The p-BVO photoanode described herein outperformed all previously reported analogs, showing JphE6.1 mA cm -2 at 1.23 VRHE after Co-Pi electrocatalyst deposition (AM1.5G illumination, 100 mW cm -2 ). The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers..